2023
DOI: 10.1186/s12859-023-05587-4
|View full text |Cite|
|
Sign up to set email alerts
|

G-bic: generating synthetic benchmarks for biclustering

Eduardo N. Castanho,
João P. Lobo,
Rui Henriques
et al.

Abstract: Background Biclustering is increasingly used in biomedical data analysis, recommendation tasks, and text mining domains, with hundreds of biclustering algorithms proposed. When assessing the performance of these algorithms, more than real datasets are required as they do not offer a solid ground truth. Synthetic data surpass this limitation by producing reference solutions to be compared with the found patterns. However, generating synthetic datasets is challenging since the generated data must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Following the publication of the original article [ 1 ], the authors identified that the funding note was incorrect. The correct funding note is given below.…”
Section: Correction: Castanho Et Al Bmc Bioinformatics ...mentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified that the funding note was incorrect. The correct funding note is given below.…”
Section: Correction: Castanho Et Al Bmc Bioinformatics ...mentioning
confidence: 99%